Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Certainly! Here's a detailed step-by-step solution to the problem:
### Given:
1. [tex]\( (5x - 1) \)[/tex] is a factor of [tex]\( 5x^3 + ax^2 + bx + 6 \)[/tex].
2. The remainder when the polynomial is divided by [tex]\( (x - 2) \)[/tex] is 72.
#### Part (a): Find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]
Since [tex]\((5x - 1)\)[/tex] is a factor of [tex]\(5x^3 + ax^2 + bx + 6\)[/tex], it implies that [tex]\(P(\frac{1}{5}) = 0\)[/tex].
Given polynomial [tex]\(P(x) = 5x^3 + ax^2 + bx + 6\)[/tex], substituting [tex]\(\frac{1}{5}\)[/tex] into [tex]\(P(x)\)[/tex]:
[tex]\[ P\left(\frac{1}{5}\right) = 5\left(\frac{1}{5}\right)^3 + a\left(\frac{1}{5}\right)^2 + b\left(\frac{1}{5}\right) + 6 = 0 \][/tex]
Simplify:
[tex]\[ 5 \left(\frac{1}{125}\right) + a \left(\frac{1}{25}\right) + b \left(\frac{1}{5}\right) + 6 = 0 \][/tex]
[tex]\[ \frac{5}{125} + \frac{a}{25} + \frac{b}{5} + 6 = 0 \][/tex]
[tex]\[ \frac{1}{25} + \frac{a}{25} + \frac{5b}{25} + 6 = 0 \][/tex]
[tex]\[ \frac{1 + a + 5b}{25} + 6 = 0 \][/tex]
[tex]\[ 1 + a + 5b + 150 = 0 \][/tex]
[tex]\[ a + 5b + 151 = 0 \][/tex]
[tex]\[ a + 5b = -151 \][/tex] ... (1)
Also, the remainder when divided by [tex]\((x - 2)\)[/tex] is 72, implying [tex]\(P(2) = 72\)[/tex]:
[tex]\[ P(2) = 5(2)^3 + a(2)^2 + b(2) + 6 = 72 \][/tex]
[tex]\[ 40 + 4a + 2b + 6 = 72 \][/tex]
[tex]\[ 46 + 4a + 2b = 72 \][/tex]
[tex]\[ 4a + 2b = 26 \][/tex]
[tex]\[ 2a + b = 13 \][/tex] ... (2)
Using equations (1) and (2), solve for [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
1. [tex]\(a + 5b = -151\)[/tex]
2. [tex]\(2a + b = 13\)[/tex]
From equation (2):
[tex]\[ b = 13 - 2a \][/tex]
Substitute [tex]\(b\)[/tex] into equation (1):
[tex]\[ a + 5(13 - 2a) = -151 \][/tex]
[tex]\[ a + 65 - 10a = -151 \][/tex]
[tex]\[ -9a = -216 \][/tex]
[tex]\[ a = 24 \][/tex]
Substituting [tex]\(a = 24\)[/tex] back into equation (2):
[tex]\[ 2(24) + b = 13 \][/tex]
[tex]\[ 48 + b = 13 \][/tex]
[tex]\[ b = -35 \][/tex]
So, the values are:
[tex]\[ a = 24 \][/tex]
[tex]\[ b = -35 \][/tex]
#### Part (b): Factorize the expression completely
Now substitute [tex]\(a\)[/tex] and [tex]\(b\)[/tex] back into the polynomial:
[tex]\[ 5x^3 + 24x^2 - 35x + 6 \][/tex]
Given that [tex]\( (5x - 1) \)[/tex] is a factor, let's divide the polynomial by [tex]\( (5x - 1) \)[/tex]:
To perform polynomial division:
1. [tex]\(5x^3 + 24x^2 - 35x + 6\)[/tex] divided by [tex]\(5x - 1\)[/tex]:
Perform the division (performing synthetic or long division):
[tex]\[ \frac{5x^3 + 24x^2 - 35x + 6}{5x - 1} = x^2 + 5x - 6 \][/tex]
So, the polynomial can be factorized as:
[tex]\[ 5x^3 + 24x^2 - 35x + 6 = (5x - 1)(x^2 + 5x - 6) \][/tex]
Factorize [tex]\(x^2 + 5x - 6\)[/tex]:
[tex]\[ x^2 + 5x - 6 = (x + 6)(x - 1) \][/tex]
So, the complete factorization is:
[tex]\[ 5x^3 + 24x^2 - 35x + 6 = (5x - 1)(x + 6)(x - 1) \][/tex]
#### Part (c): Solve the equation [tex]\(5x^3 + 24x^2 - 35x + 6 = 0\)[/tex]
Using the factorized form:
[tex]\[ (5x - 1)(x + 6)(x - 1) = 0 \][/tex]
Set each factor to zero:
1. [tex]\(5x - 1 = 0 \Rightarrow x = \frac{1}{5}\)[/tex]
2. [tex]\(x + 6 = 0 \Rightarrow x = -6\)[/tex]
3. [tex]\(x - 1 = 0 \Rightarrow x = 1\)[/tex]
So, the solutions are:
[tex]\[ x = \frac{1}{5}, x = -6, x = 1 \][/tex]
Therefore, the roots of the polynomial [tex]\(5x^3 + 24x^2 - 35x + 6 = 0\)[/tex] are:
[tex]\[ \boxed{\frac{1}{5}, -6, 1} \][/tex]
### Given:
1. [tex]\( (5x - 1) \)[/tex] is a factor of [tex]\( 5x^3 + ax^2 + bx + 6 \)[/tex].
2. The remainder when the polynomial is divided by [tex]\( (x - 2) \)[/tex] is 72.
#### Part (a): Find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]
Since [tex]\((5x - 1)\)[/tex] is a factor of [tex]\(5x^3 + ax^2 + bx + 6\)[/tex], it implies that [tex]\(P(\frac{1}{5}) = 0\)[/tex].
Given polynomial [tex]\(P(x) = 5x^3 + ax^2 + bx + 6\)[/tex], substituting [tex]\(\frac{1}{5}\)[/tex] into [tex]\(P(x)\)[/tex]:
[tex]\[ P\left(\frac{1}{5}\right) = 5\left(\frac{1}{5}\right)^3 + a\left(\frac{1}{5}\right)^2 + b\left(\frac{1}{5}\right) + 6 = 0 \][/tex]
Simplify:
[tex]\[ 5 \left(\frac{1}{125}\right) + a \left(\frac{1}{25}\right) + b \left(\frac{1}{5}\right) + 6 = 0 \][/tex]
[tex]\[ \frac{5}{125} + \frac{a}{25} + \frac{b}{5} + 6 = 0 \][/tex]
[tex]\[ \frac{1}{25} + \frac{a}{25} + \frac{5b}{25} + 6 = 0 \][/tex]
[tex]\[ \frac{1 + a + 5b}{25} + 6 = 0 \][/tex]
[tex]\[ 1 + a + 5b + 150 = 0 \][/tex]
[tex]\[ a + 5b + 151 = 0 \][/tex]
[tex]\[ a + 5b = -151 \][/tex] ... (1)
Also, the remainder when divided by [tex]\((x - 2)\)[/tex] is 72, implying [tex]\(P(2) = 72\)[/tex]:
[tex]\[ P(2) = 5(2)^3 + a(2)^2 + b(2) + 6 = 72 \][/tex]
[tex]\[ 40 + 4a + 2b + 6 = 72 \][/tex]
[tex]\[ 46 + 4a + 2b = 72 \][/tex]
[tex]\[ 4a + 2b = 26 \][/tex]
[tex]\[ 2a + b = 13 \][/tex] ... (2)
Using equations (1) and (2), solve for [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
1. [tex]\(a + 5b = -151\)[/tex]
2. [tex]\(2a + b = 13\)[/tex]
From equation (2):
[tex]\[ b = 13 - 2a \][/tex]
Substitute [tex]\(b\)[/tex] into equation (1):
[tex]\[ a + 5(13 - 2a) = -151 \][/tex]
[tex]\[ a + 65 - 10a = -151 \][/tex]
[tex]\[ -9a = -216 \][/tex]
[tex]\[ a = 24 \][/tex]
Substituting [tex]\(a = 24\)[/tex] back into equation (2):
[tex]\[ 2(24) + b = 13 \][/tex]
[tex]\[ 48 + b = 13 \][/tex]
[tex]\[ b = -35 \][/tex]
So, the values are:
[tex]\[ a = 24 \][/tex]
[tex]\[ b = -35 \][/tex]
#### Part (b): Factorize the expression completely
Now substitute [tex]\(a\)[/tex] and [tex]\(b\)[/tex] back into the polynomial:
[tex]\[ 5x^3 + 24x^2 - 35x + 6 \][/tex]
Given that [tex]\( (5x - 1) \)[/tex] is a factor, let's divide the polynomial by [tex]\( (5x - 1) \)[/tex]:
To perform polynomial division:
1. [tex]\(5x^3 + 24x^2 - 35x + 6\)[/tex] divided by [tex]\(5x - 1\)[/tex]:
Perform the division (performing synthetic or long division):
[tex]\[ \frac{5x^3 + 24x^2 - 35x + 6}{5x - 1} = x^2 + 5x - 6 \][/tex]
So, the polynomial can be factorized as:
[tex]\[ 5x^3 + 24x^2 - 35x + 6 = (5x - 1)(x^2 + 5x - 6) \][/tex]
Factorize [tex]\(x^2 + 5x - 6\)[/tex]:
[tex]\[ x^2 + 5x - 6 = (x + 6)(x - 1) \][/tex]
So, the complete factorization is:
[tex]\[ 5x^3 + 24x^2 - 35x + 6 = (5x - 1)(x + 6)(x - 1) \][/tex]
#### Part (c): Solve the equation [tex]\(5x^3 + 24x^2 - 35x + 6 = 0\)[/tex]
Using the factorized form:
[tex]\[ (5x - 1)(x + 6)(x - 1) = 0 \][/tex]
Set each factor to zero:
1. [tex]\(5x - 1 = 0 \Rightarrow x = \frac{1}{5}\)[/tex]
2. [tex]\(x + 6 = 0 \Rightarrow x = -6\)[/tex]
3. [tex]\(x - 1 = 0 \Rightarrow x = 1\)[/tex]
So, the solutions are:
[tex]\[ x = \frac{1}{5}, x = -6, x = 1 \][/tex]
Therefore, the roots of the polynomial [tex]\(5x^3 + 24x^2 - 35x + 6 = 0\)[/tex] are:
[tex]\[ \boxed{\frac{1}{5}, -6, 1} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.